2007
DOI: 10.1108/17410400810841209
|View full text |Cite
|
Sign up to set email alerts
|

Lives in the balance: an analysis of the balanced scorecard (BSC) in healthcare organizations

Abstract: Purpose -The purpose of this paper is to show how the balanced scorecard (BSC) has been a prominent innovation in strategic performance measurement systems. The health care sector has started to adopt this approach. Design/methodology/approach -There are many case studies of BSC applications and this paper reviews this literature to analyse the application of the BSC across this sector. In particular, it is argued that the current applications do not tend to show the health of patients as being central in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
87
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(91 citation statements)
references
References 20 publications
1
87
0
3
Order By: Relevance
“…Table 1 illustrates the general vision of the public health system in Brazil (SUS) and the strategic objectives for each BSC perspective, as derived from some literature references [31]–[36].…”
Section: Methodsmentioning
confidence: 99%
“…Table 1 illustrates the general vision of the public health system in Brazil (SUS) and the strategic objectives for each BSC perspective, as derived from some literature references [31]–[36].…”
Section: Methodsmentioning
confidence: 99%
“…The balanced scorecard (BSC) has been and still is a prominent innovation in strategic performance measurement systems (Gurd and Gao, 2007). Considering the four mentioned strategic axes, in this paper we will adapt the BSC for economic entities to the specific of the non-profit organizations which are involved in education.…”
Section: A Bsc Analysis: For-profit Entities Versus Non-profit Organimentioning
confidence: 99%
“…By the time the report was produced the information was often outdated and new measurements had to take place (c.f. Gurd and Gao, 2008).…”
Section: What Are the Main Issues With Measuring And Reporting Operatmentioning
confidence: 99%
“…Kennerley and Neely's review of the literature (2003) showed evidence that organisations implementing 'integrated balanced performance management systems' outperform others that do not. Gurd and Gao (2008), in their review of strategic performance measurement systems within healthcare, found diverse forms of the BSC with varying measures being used. The Balanced Scorecard (Kaplan and Norton, 2001;1996;1992), the SMART (Strategic Measurement Analysis and Reporting Technique) system and its embodiment, the performance pyramid (Lynch and Cross, 1991) and the Integrated Dynamic Performance Measurement System (Ghalayini et al, 1997) connect operational performance with the strategic goals of the organisation.…”
Section: Introductionmentioning
confidence: 99%